Auditing Palliative Care Provided by Nurses for Chronic Pain Management in the Elderly - Ebrahimi, Nazli; Naderi, Manijeh; Atashzadeh-Shoorideh, Foroozan; Ilkhani, Mahnaz; Shakeri, Nezhat (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Pain is the most common mental pressure in the elderly and its abstract nature makes it a challenging subject to study. Conformity of palliative care management was examined with standards. Methods: Through a descriptive audit study, 210 elderly patients with chronic pain, who were candidates for palliative and curative care, were examined. A researcher-designed checklist of standard health care for pain management and McGill pain questionnaire were used for data gathering. Data analyses were performed using descriptive statistics and estimating conformity of the pain management measures with standards of SPSS (18). Results: Checking records of painkillers (60%) and reporting the patient’s pain to the physician (74.8%) were the most efficient palliative and curative measures, respectively. Surveying pain (41.9%) and introducing oneself to the patient (42.4%) were the least efficient healthcare services. In addition, palliative measures (24.73%) and drug-intervention measures (30.93%) had little conformity with the pain management standards. Conclusions: Pain management care provided for the elderly has a long way to meet standards. This notable difference can be rooted in the abstract nature of pain and lack of knowledge of the medical team about palliative and curative measures for pain management